Evaluation of effluent quality in water treatment plants in the Ipojuca River basin - Silva, Luane Lins da; Silva, Vicente de Paulo; Arruda, Valmir Cristiano Marques de; Beltrame, Leocádia Terezinha Cordeiro; Moraes, Alex Souza (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
This study aimed to evaluate the physical-chemical and microbiological parameters of the sewage treatment plants in the municipalities of Tacaimbó, Rendeiras, and Gravatá in the state of Pernambuco, using descriptive and multivariate statistics and a computer tool. The parameters analyzed were provided by Pernambuco’s Water and Sanitation Company (COMPESA), with all samples collected during 2020. The analysis results were compared to the values recommended by current federal and state environmental legislation. The assessment of the quality of effluents from the Ipojuca River basin helped analyze the contribution made by the Environmental Sanitation Program to the depollution of the Ipojuca River basin’s waters. By analyzing the descriptive statistics of the effluent quality parameters, it can be generally concluded that the STPs studied meet the requirements defined by the environmental agencies, especially regarding organic matter removal. Using multivariate statistics, it was possible to conclude that the most significant variation in the data is related to the parameters that represent pollution (organic matter). This occurrence may represent failures in collection and storage procedures and inefficient operation at certain times of the year. The proper operation of sewage treatment systems is essential for maintaining the environmental quality of water bodies.